Dimensions of Imagery: Translation Analysis on the Example of “The Lion, The Witch and The Wardrobe” - Feret, Magdalena Zofia Zofia (Respectus Philologicus, 2017)
The aim of this paper is to show how imagery, one of the most important human cognitive abilities, can be expressed. It considers the impact this ability can have on the process of text production and its understanding in translation. The cognitive grammar model by Ronald Wayne Langacker (1987, 1991) has formed the methodological perspective. The application of cognitive translation theory to translation analysis is presented on the example of the novel by Clive Staples Lewis The Lion, the Witch and the Wardrobe and its translation into Polish by Andrzej Polkowski and into German by Lisa Tetzner. First of all, the terms ‘conceptualisation’ and ‘imagery’ are introduced and explained from the cognitive perspective. Then, the dimensions of imagery – selection, abstraction and perspective – are described. Based on this, the examples selected from the novel The Lion, the Witch and the Wardrobe and its Polish and German translations are analysed and the results are discussed.